Spatio-Temporal Regulation of RhoGTPases Signaling by Myosin II - Wu, Selwin K.; Priya, Rashmi (Frontiers in Cell and Developmental Biology, 2019)
RhoGTPase activation of non-muscle myosin II controls many cellular processes including cell division, extrusion, adhesion, migration, intracellular transport, and tissue morphogenesis. However, the regulation of Myosin II and signaling is not that straightforward. Increasingly, we have come to appreciate the role of Myosin II on the feedback regulation of RhoGTPase signaling. Indeed, Myosin II controls RhoGTPase signaling through multiple mechanisms namely contractility driven advection, scaffolding, and sequestration of signaling molecules. Here we discuss these mechanisms by which Myosin II regulates RhoGTPase signaling in cell adhesion, migration, and tissue morphogenesis.